A study of Islamic calligraphy in Malacca mosque / Mohd Azwan Ab Aziz - Ab Aziz, Mohd Azwan (2019)
Mosque is a special and proper place of worship such as prayer and „Ikhtikaf‟ contemplation for Muslims. The building is also served as a cultural centre, transactions and developments as well as the centre of Islamic propagation activities of Muslims. A mosque does not have fixed architectural design to be followed, but depends on the culture of the local Islamic community. The research is done to study the calligraphy art in five from 56 heritage mosque in Malacca.